Lamellar ichthyosis with genu valgum: unfolding the link. (22nd November 2012) - Deka, Nilakshi; Sarma, Dipti; Saikia, Uma Kaimal
Abstract : We describe a case of lamellar ichthyosis with bilateral genu valgum. The association of genu valgum with congenital ichthyosis is rare. Our patient, a 22-year-old girl, had lamellar ichthyosis and was born with a collodion membrane. She developed progressive valgus deformity of the knees of 5 years duration associated with difficulty in walking. On evaluation, she had generalised scaly skin lesions along with bilateral genu valgum and biochemical evidence of vitamin D deficiency. Skin serves as an important site for vitamin D synthesis and thus skeletal deformities secondary to vitamin D deficiency may occur in cases of congenital ichthyosis, causing a diagnostic dilemma due to the unusual association. This case serves as a reminder that clinicians need to be aware of such an association in order to prevent, appropriately diagnose and adequately treat the rare case of congenital ichthyosis with rickets and osteomalacia.